SOBRE LA HISTOPATOLOGIA DE LA EPILEPSIA MIOCLONICA Y DE LAS MIOCLONIAS SIMPLES - VILLA SANA, ANTONIO; NIETO, DIONISIO (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1945)
A histopathologic study of a human brain following prefrontal lobectomy showed degeneration of the dorsomedial nucleus of the thalamus
BOL INST ESTUD MED BIOL
Keywords: HISTOPATOLOGIA, EPILEPSIA, MIOCLONICA, MIOCLONIAS; CIENCIAS MEDICAS; BIOLOGIA CELULAR